1992
DOI: 10.1111/j.1744-7348.1992.tb03981.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial antibiosis to Rhopalosiphum padi in wheat and some phytochemical correlations

Abstract: The fecundity of the aphid Rhopalosiphum padi during the first ten days of reproduction was measured on five wheats at three growth stages. The wheats were of UK and Iranian origin, but also involved both spring and winter wheats as well as hexaploid and tetraploid types. Aphids which had already been reared on the respective variety for at least one generation were transferred to the experimental plants. The tetraploid Emmer showed some resistance in comparison with the hexaploid UK varieties at later growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 14 publications
2
27
4
Order By: Relevance
“…For example, A. fabae performance was positively correlated with the concentration of protein and nonprotein amino acids in Vicia species (Holt and Birch 1984), and the concentration of the 10 essential amino acids were higher in susceptible P. sativum plants than in resistant varieties, with the difference for ASN and ASP being the greatest (Auclair 1976). However, and in contrast with our results, wheat cultivars resistant to Rhopalosiphum padi had high levels of ALA, HIS, and THR (Kazemi and Van Emden 1992), and GLU was negatively associated with R. padi performance (Weibull 1994). In addition, in a cucurbit species (melon, Cucumis melo L.), GLU was higher in the Aphis gossypiiÐresistant line than in the susceptible line (Chen et al 1997).…”
Section: Stagecontrasting
confidence: 86%
See 1 more Smart Citation
“…For example, A. fabae performance was positively correlated with the concentration of protein and nonprotein amino acids in Vicia species (Holt and Birch 1984), and the concentration of the 10 essential amino acids were higher in susceptible P. sativum plants than in resistant varieties, with the difference for ASN and ASP being the greatest (Auclair 1976). However, and in contrast with our results, wheat cultivars resistant to Rhopalosiphum padi had high levels of ALA, HIS, and THR (Kazemi and Van Emden 1992), and GLU was negatively associated with R. padi performance (Weibull 1994). In addition, in a cucurbit species (melon, Cucumis melo L.), GLU was higher in the Aphis gossypiiÐresistant line than in the susceptible line (Chen et al 1997).…”
Section: Stagecontrasting
confidence: 86%
“…The amino acid composition of the phloem has also been related with aphid host plant resistance. Studies in cereal crops including oats, barley, rice, and wheat have shown that speciÞc amino acids are correlated with resistance to aphids (Weibull 1988(Weibull , 1994Kazemi and Van Emden 1992). Studies in legumes like Vicia faba L. (Holt and Birch 1984) and Pisum sativum (Auclair 1976) suggest a potential role for total content of free amino acids and amino acids composition in aphid resistance.…”
mentioning
confidence: 96%
“…For instance, hydroxamic acids showed no correlation with a variable response to R. padi fecundity of five wheat varieties (representing UK and Iranian origin and tetra and hexaploid what) at tillering stage (Kazemi and Emden 1992). Addition-ally, levels of hydroxamic acids in tetra-and hexaploid wheat did not correlate with R. padi settlement and reproduction (Elek et al 2013a).…”
Section: Discussionmentioning
confidence: 93%
“…While Myzus persicae Sulz. needs Met and g-amino butyric acid (GABA), the amino acids Thr, His and alanine (Ala) are important for Rhopalosiphum padi Koch (Kazemi & Emden 1992).…”
Section: Introductionmentioning
confidence: 99%